URGENSI PENETAPAN WAKTU PECARUAN PADA TILEM KESANGA: TINJAUAN TEKSTUAL, ASTRONOMIS, DAN FILOSOFIS - Ida Kade Suarioka; Ida Bagus Made Sadu Gunawan; I Gusti Agung Paramita (FAKULTAS ILMU AGAMA DAN KEBUDAYAAN, 2025)
The implementation of Pecaruan on Tilem Kesanga is not an arbitrary provision that can be changed simply for convenience or practicality. This provision has a solid foundation in three dimensions: the textual authority of classical palm-leaf manuscripts that explicitly stipulate the time; astronomical justification indicating that Tilem Kesanga is a cosmic moment when the lunar phase and the optimal solar position converge; a philosophical foundation that teaches the importance of harmony between human actions (Karma) and the right time (Kala) in accordance with the laws of the universe (Rta). The discourse to shift the implementation time to Purwaning Tilem Kesanga requires careful examination, given its profound theological, cosmological, and philosophical implications. The decision to change a centuries-old tradition should not be made without a comprehensive study involving a deep understanding of the Wariga system as a science of cosmic harmony.